Isotopic and chemical variation of organic nanoglobules in primitive meteorites. (30th April 2013) - De Gregorio, Bradley T.; Stroud, Rhonda M.; Nittler, Larry R.; Alexander, Conel M. O'D.; Bassim, Nabil D.; Cody, George D.; Kilcoyne, A. L. David; Sandford, Scott A.; Milam, Stefanie N.; Nuevo, Michel; Zega, Thomas J.
Abstract Organic nanoglobules are microscopic spherical carbon‐rich objects present in chondritic meteorites and other astromaterials. We performed a survey of the morphology, organic functional chemistry, and isotopic composition of 184 nanoglobules in insoluble organic matter (IOM) residues from seven primitive carbonaceous chondrites. Hollow and solid nanoglobules occur in each IOM residue, as well as globules with unusual shapes and structures. Most nanoglobules have an organic functional chemistry similar to, but slightly more carboxyl‐rich than, the surrounding IOM, while a subset of nanoglobules have a distinct, highly aromatic functionality. The range of nanoglobule N isotopic compositions was similar to that of nonglobular 15N‐rich hotspots in each IOM residue, but nanoglobules account for only about one third of the total 15N‐rich hotspots in each sample. Furthermore, many nanoglobules in each residue contained no 15N enrichment above that of bulk IOM. No morphological indicators were found to robustly distinguish the highly aromatic nanoglobules from those that have a more IOM‐like functional chemistry, or to distinguish 15N‐rich nanoglobules from those that are isotopically normal. The relative abundance of aromatic nanoglobules was lower, and nanoglobule diameters were greater, in more altered meteorites, suggesting the creation/modification of IOM‐like nanoglobules during parent‐body processing. However, 15N‐rich nanoglobules, including many with highly aromatic functional chemistry, likely reflect preaccretionary isotopic fractionation in cold molecular cloud or protostellar environments. These data indicate that no single formation mechanism can explain all of the observed characteristics of nanoglobules, and their properties are likely a result of multiple processes occurring in a variety of environments.